Invasive Gram-negative bacilli are frequently resistant to standard antibiotics for children admitted to hospital in Kilifi, Kenya. - Bejon, P; Mwangi, I; Ngetsa, C; Mwarumba, S; Berkley, J; Lowe, B; Maitland, K; Marsh, K; English, M; Scott, J (2005)
OBJECTIVES: To determine the pattern of resistance among Gram-negative bacilli causing invasive bacterial disease for the antibiotics that are already in common use in Kilifi, Kenya and for two potential alternatives, ciprofloxacin and cefotaxime. Also, to determine whether prevalence and severity of resistance was increasing over time, to identify patients who are particularly at risk of resistant infections, and to explore which factors are associated with the development of resistance in our setting. METHODS: We used Etest to study antibiotic susceptibility patterns of 90 Gram-negative bacilli cultured in blood or CSF from paediatric inpatients over 8 years. RESULTS: Susceptibility to amoxicillin 28%, cefotaxime 95% and ciprofloxacin 99% did not vary significantly with age. Susceptibilities for isolates from children aged less than 14 days were: chloramphenicol, 81%; trimethoprim/sulfamethoxazole, 71%; and gentamicin, 91%. From older children, susceptibilities were: chloramphenicol, 62%; trimethoprim/sulfamethoxazole, 39%; and gentamicin, 73%. Chloramphenicol susceptibility was significantly more common among non-typhi salmonellae than other species (79% versus 53%, P < 0.0005). The combination of gentamicin and chloramphenicol covered 91% of all isolates. The prevalence of resistance did not increase over time and was not more common in patients with HIV or malnutrition. Age was the only clinical feature that predicted resistance. CONCLUSIONS: Gentamicin or chloramphenicol alone was suboptimal therapy for Gram-negative sepsis, although in this retrospective study, there was no association between resistance and mortality.